Studi Kelayakan Pembangkit Listrik Tenaga Micro Hydro Di Sungai Manare Kampung Ambaidiru Distrik Kosiwo Kabupaten Kepulauan Yapen - Henny Lesnussa; Yulianus Rombe Pasalli; Daniel Manyamboi (Universitas Nusa Putra, 2023)
The research was conducted with the aim of providing data, information, and potential for Micro Hydro Power Plant (PLTMH) in the Manare River. It is hoped that this research will be useful as a source of source of literature to the people of Ambaidiru village and the building management of PLTMH in order to develop natural resources in the Yapen Islands regency. The research was conducted by measuring potential data in the form of discharge and head, followed by research on the condition of the PLTMH location. The collected data is then analyzed as a basis to determine the type of turbine at PLTMH, with an emphasis on construction works, engine work, and electrical installations from PLTMH. The calculation results with a discharge of 0.2912 m3/s and a head of 12 meters, resulted in 23.996 kW power flown. Calculation of intake dimensions 0.149 m3, garbage filter size larger than the intake and using iron with an area of 0.297 m2, carrier channel area 0.418 m2, settling tub size 1.5 m x 3 m, depth 2 m made from masonry, made on a turbine pool, turbine pool from concrete diameter 0.64 m depth 1 m, pipe used PVC pipe type AW gray thick, diameter 6 inches, disposable channel of split stone. The mechanical installation uses a crossflow turbine and a kaplan turbine with a power of 34,280 kW. The specific speed of the turbine is 927, with the turbine rotation of 1000 rpm.